Long-Term Efficacy of AAV9-U7snRNA-Mediated Exon 51 Skipping in mdx52 Mice - Philippine Aupy; Faouzi Zarrouki; Quentin Sandro; Cécile Gastaldi; Pierre-Olivier Buclez; Kamel Mamchaoui; Luis Garcia; Cyrille Vaillend; Aurélie Goyenvalle (Molecular Therapy: Methods & Clinical Development, 2020)
Gene therapy and antisense approaches hold promise for the treatment of Duchenne muscular dystrophy (DMD). The advantages of both therapeutic strategies can be combined by vectorizing antisense sequences into an adeno-associated virus (AAV) vector. We previously reported the efficacy of AAV-U7 small nuclear RNA (U7snRNA)-mediated exon skipping in the mdx mouse, the dys−/utr− mouse, and the golden retriever muscular dystrophy (GRMD) dog model. In this study, we examined the therapeutic potential of an AAV-U7snRNA targeting the human DMD exon 51, which could be applicable to 13% of DMD patients. A single injection of AAV9-U7 exon 51 (U7ex51) induces widespread and sustained levels of exon 51 skipping, leading to significant restoration of dystrophin and improvement of the dystrophic phenotype in the mdx52 mouse. However, levels of dystrophin re-expression are lower than the skipping levels, in contrast with previously reported results in the mdx mouse, suggesting that efficacy of exon skipping may vary depending on the targeted exon. Additionally, while low levels of exon skipping were measured in the brain, the dystrophin protein could not be detected, in line with a lack of improvement of their abnormal behavioral fear response. These results thus confirm the high therapeutic potential of the AAV-mediated exon-skipping approach, yet the apparent discrepancies between exon skipping and protein restoration levels suggest some limitations of this experimental model.